2002
DOI: 10.1073/pnas.182418399
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a human telomerase reverse transcriptase peptide of low affinity for HLA A2.1 that induces cytotoxic T lymphocytes and mediates lysis of tumor cells

Abstract: Telomerase reverse transcriptase (TRT) is a tumor-associated antigen expressed in the vast majority of human tumors and is presently one of the most promising target candidates for a therapeutic cancer vaccine. TRT is also expressed at low level in selected tissues and should be considered a self antigen. In the present study we sought to develop cytotoxic T lymphocytes (CTL) responses directed against human (h)TRT peptides with low relative affinity for which the available repertoire is to be preferentially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 52 publications
3
75
0
3
Order By: Relevance
“…The therapeutic strategies under investigation include functional inhibition by genetic and pharmacologic approaches (15,16,18,19) as well as immunotherapy (20). hTERT contains several HLA-restricted-binding motifs that have been used to generate tumoricidal CTLs (21)(22)(23). Minev et al found that immunization of patients with prostate cancer with two HLA-A*0201 + -restricted peptides from hTERT, p540 (ILAKFLHWL) and p865 (RLVDDFLLV), developed hTERT-specific CTLs that specifically lysed a variety of HLA-A*0201 + cancer cell lines (24).…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic strategies under investigation include functional inhibition by genetic and pharmacologic approaches (15,16,18,19) as well as immunotherapy (20). hTERT contains several HLA-restricted-binding motifs that have been used to generate tumoricidal CTLs (21)(22)(23). Minev et al found that immunization of patients with prostate cancer with two HLA-A*0201 + -restricted peptides from hTERT, p540 (ILAKFLHWL) and p865 (RLVDDFLLV), developed hTERT-specific CTLs that specifically lysed a variety of HLA-A*0201 + cancer cell lines (24).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that T cells of the human immune system can recognise hTERT peptides, and a number of HLA-class I and class II epitopes have been characterised (Vonderheide et al, 1999;Minev et al, 2000;Arai et al, 2001;Vonderheide et al, 2001;Hernandez et al, 2002;Scardino et al, 2002;Schroers et al, 2002Schroers et al, , 2003Gross et al, 2004). Recently it has also been reported that telomerase-specific CD4 þ and CD8 þ T-cell responses are induced upon vaccination with hTERT-transfected dendritic cells (Su et al, 2005).…”
mentioning
confidence: 99%
“…These include epitopes restricted to HLA-A2 as well as HLA-A1, -A3, -A24, and -B7 [41,[48][49][50][51][52][53][54][55][56]. More than 90% of humans express at least one of these five MHC class I alleles.…”
Section: Immunological Characterization Of Htert-derived T Cell Epitopesmentioning
confidence: 99%
“…Classically considered poorly immunogenic, low-affinity epitopes can induce robust CTL responses after modification from wild type sequence, for example, by changing position 1 of HLA-A2-restricted peptide epitopes to tyrosine [60]. Two such low-affinity HLA-A2-restricted epitopes derived from hTERT are 572Y (YLFFYRKSV) and 988Y (YLQVNSLQTV) [50,51] and each exhibits strong affinity for HLA-A2 and stimulates specific CTL in vitro. These CTL specifically lyse hTERT-expressing tumor cells of various histologies but not HLA-A2-negative or hTERT-negative tumors [50,51].…”
Section: Immunological Characterization Of Htert-derived T Cell Epitopesmentioning
confidence: 99%